Factors Influencing Attitude toward Online Advertising in Kathmandu Valley - Devkota, Niranjan; Bijukshe, Aayush; Pokhrel, Laxman; Paudel, Udaya Raj; Parajuli, Seeprata (PYC Nepal Journal of Management, 2021)
The paper investigates attitude towards online advertising in Kathmandu Valley. The paper adopted descriptive cross-sectional research design and non- probability sampling technique to collect data. Data were collected from 401 online shopping customers of Kathmandu Valley. PLS based structural equation model was applied to examine the hypotheses. First, the study examined the relationship between good for economy elements and attitude toward online advertising, result confirms that the good for economy elements have a significant influence on the attitude toward advertising in online platforms. This paper also examined the relationship between quality elements and attitude toward online advertising and found that good quality elements of advertisement have a significant influence on attitudes toward online advertising in online platforms. Findings suggest that good for the economy and quality elements of online advertising have a significant influence on attitudes toward online advertisements.